Resultater ved fronten – brugen af effektstyring i dagtilbud - Grøn, Caroline Howard (Politik, 2015)
The article illustrates how management by objectives is practiced in everyday life in the Danish public sector. By analysing use of a management-by-objectives-inspired tool in everyday practices by employees in day-care in a Danish municipality, the article shows how the same managerial impulse can result in remarkably dif- ferent actions at street-level. While some employees do noting faced with the managerial initiatives others do very di erent things with the same initiative as point of reference. Variations in use can partly be explained by local managerial support, the local organization of work and the existing of competing agendas which crave employee attention. e article clearly illustrates how a coherent tool at administrative level can be transformed in to numerous di erent tools in practice.